2016
DOI: 10.1007/s12224-016-9241-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Landscape Structure and Socio-Economic Variables Explain the Solidago Invasion?

Abstract: Biological invasions are considered a major threat to biodiversity on a global scale. In this study, we examined the effect of landscape structure and socioeconomic variables on the invasion pattern of alien Solidago species. Field data were collected in a set of 309 sampling plots, regularly placed on the intersecting lines of a 10 × 10-km grid, in south-western Poland (Silesia, Central Europe). Landscape characteristics and average values of socio-economic variables, such as human population density and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…The most invasive among the studied taxa ( S. canadensis and S. gigantea ) exhibited rather moderate levels of phenotypic plasticity while producing high amounts of biomass. It should be noted that the nitrogen content of the different substrates was too low to induce growth in the examined plants; however, the results of field studies have shown that the difference in nitrogen content ranging from 0.55 to 4.69 g/kg was positively correlated with ramet height in S. gigantea (Szymura et al, ; M. Szymura, 2007). These results suggest that the two species can be considered as a “Jack of all traits and master of some” type.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The most invasive among the studied taxa ( S. canadensis and S. gigantea ) exhibited rather moderate levels of phenotypic plasticity while producing high amounts of biomass. It should be noted that the nitrogen content of the different substrates was too low to induce growth in the examined plants; however, the results of field studies have shown that the difference in nitrogen content ranging from 0.55 to 4.69 g/kg was positively correlated with ramet height in S. gigantea (Szymura et al, ; M. Szymura, 2007). These results suggest that the two species can be considered as a “Jack of all traits and master of some” type.…”
Section: Discussionmentioning
confidence: 98%
“…By using different substrates, we obtained three levels of fertility: high (horticultural), moderate (local soil) and poor (mixture of local soil with sand and gravel). The range of chemical properties of the substrates corresponded to the soils on which goldenrods were found in the fields of central Europe (Szymura et al, ; Szymura & Szymura, ); the pH was similar among all three substrates. The substrate properties are detailed in Table .…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Although a global unifying theory is still lacking, several modeling approaches have proved to be useful to predict the distribution of invasive species (reviewed by Higgins and Richardson, 1996;Gallien et al, 2010;Hui et al, 2011). Some attempts have been made to predict the 'invasiveness' of organisms, as well as the invasibility of ecosystems (Barrat-Segretain et al, 2002;Hovick et al, 2012;Szymura et al, 2016). General concepts from community ecology can also be used for invasive species, and their distributions can be predicted, for example, using empirical habitat suitability models or by niche modeling based on species attributes (Thuiller et al, 2005;Buisson et al, 2008;Sharma et al, 2011;Marras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%